Anaesthetic drug administration as a potential contributor to healthcare-associated infections: a prospective simulation-based evaluation of aseptic techniques in the administration of anaesthetic drugs. Issue 10 (16th June 2012) - Gargiulo, Derryn A; Sheridan, Janie; Webster, Craig S; Swift, Simon; Torrie, Jane; Weller, Jennifer; Henderson, Kaylene; Hannam, Jacqueline; Merry, Alan F
Abstract : Objective: To evaluate the possibility that anaesthetists are administering potentially pathogenic micro-organisms to their patients. Design: Prospective microbiological and observational study in a realistic simulated setting. Participants: Ten anaesthetists supported by 10 anaesthetic technicians. Primary outcome measure: The presence or absence of organisms cultured from sterile intravenous bags used to collect drugs injected during the simulated cases and from the needles and the contents of the syringes used. The authors also observed the aseptic techniques used. Results: Organisms were isolated from five of 38 (13%) bags from five of 20 simulated cases anaesthetised by four of 10 anaesthetists, 10 of 197 (5%) syringes and six of 17 (35%) needles. None of the anaesthetists washed their hands prior to entry, used the hand gel provided, disinfected the phial septa before drawing up drugs or disinfected the intravenous ports on the intravenous administration set before use. One was seen to recap a needle left on a syringe for possible reuse. Three participants were observed to place equipment such as stethoscopes, drug charts and pens on top of their inuse drug trays. Conclusion: The administration of intravenous drugs during anaesthesia may be an important factor in the genesis (or potentially the prevention) of healthcare-associated infection. These observations suggest room for improvement in the aseptic techniques of at least some anaesthetists when preparing and administering intravenous drugs. Confirmation of these findings in clinical settings is needed. Study registry number (for the VASER study): Australian New Zealand Clinical Trials Registry: Ref: ACTRN 12609000530224, https://www.anzctr.org.au/registry/trial_review.aspx?ID=308128 ; note that the work presented here is a subset of the registered trial and its outcomes were not included in this registration.